The alchemy of educational reform discourses in contemporary Taiwan: translation processes, limits, and the political - Lin, Yu-Chen (Cogent education, 2024)
Contemporary educational reform discourses in Taiwan call for the modernization of education to meet the needs of society of the 21 st century. The principles and rules of 'reason' that historically order educational discourses can't be taken for granted. This article uses Popkewitz's notion of alchemy to think about the principles. The notions of democracy and globalization provide the analytic 'tools' to consider the processes of translation from political programs to educational reform discourses. It is argued that ironically the translation models of educational reform require a particular epistemological structuring of agency, but while recognizing how it does not produce harmony of what is being told in political programs. Three ways of thinking about the alchemy of political in educational reform discourses are offered. It then turns to the delineation of the changing role of teachers, students, and the textbooks that mapped the 'modern' child in educational reform discourses. The apparent paradox that evidences the limits of current discourses about democracy and globalization, then, has a critical reflection.